Ask Question
23 June, 06:33

How do I solve for n in this equation:

-6n-20=-2n+4 (1-3n)

+2
Answers (1)
  1. 23 June, 08:08
    0
    -6n-20=-2n+4 (1-3n)

    Solution

    The bracket should be expanded

    -6n-20=-2n+4-12n

    Then we collect the like terms

    -6n + 2n+12n = 20+4

    8n=24

    Now divide both sides by 8

    8n/8 = 24/8

    n = 3

    You can now insert 3 into anywhere you see n and see how it goes

    -6n-20 = - 2n + 4 (1-3n)

    -6 (3) - 20 = - 2 (3) + 4[ 1-3 (3) ]

    -18 - 20 = - 6 + 4 (1-9)

    -38 = - 6 - 32

    -38 = - 38

    That's all
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “How do I solve for n in this equation: -6n-20=-2n+4 (1-3n) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers